Influence of silica source in the catalytic activity and heterogenity of mesoporous vanadosilicates - Shylesh, S.; Mirajkar, Subhash P.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2005)
Vanadium-substituted ordered mesoporous silicates (V-OMS) were synthesized hydrothermally using two common silica sources, viz. fumed silica and tetraethyl orthosilicate, and their surface properties and catalytic activities were evaluated in the liquid phase oxidation of 1-napthol using aqueous H2O2 as an oxidant. The catalysts were characterized by XRD, N-2, adsorption-desorption, DRUV-vis and TPR to evaluate the mesostructural ordering and the local environment of vanadium in the MCM-41 matrix. Characterization data of the fresh calcined catalysts reveal a more ordered hexagonal structure for the V-MCM-41 catalyst prepared by using tetraethyl orthosilicate as the silica source while spent catalyst showed that the material is less stable than the V-MCM-41 catalyst prepared by using fumed silica as the silica source. Further, the observed differences in the selectivity behavior of extracted and calcined forms of both vanadium catalysts shows that the treatment conditions had a decisive role in the formation of extra framework metal species and further in the mesoscopic structural ordering. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 1-napthol; MCM-41; Mesoporous; Oxidation; Vanadium

An improved one-pot synthesis of polydichlorophosphazene from ammonium sulfate and phosphorus pentachloride and assessment of its stability in solution - Yadav, Abhay; Yadav, Prashant; Newale, S. P.; Srivastav, V.; Singh, A. P.; Shanmuganathan, Kadhiravan; Sikder, Nirmala (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2025)
Polyphosphazenes, with their synthetic flexibilities, can be tailored to achieve various desirable properties. The synthesis of basic linear polymer polydichlorophosphazene (PDCP) free of branching and crosslinking is the most challenging step, and its extreme sensitivity to moisture makes storage and handling difficult. In the reaction of (NH4)2SO4and PCl5 (1:4.5 mole ratio) via one-pot two-step method, the monomer [Cl3PNP(O)Cl2] synthesized from the 1st step directly undergoes bulk polycondensation (2nd step) to produce PDCP. Due to impurities, the produced PDCP is afflicted by frequent branching, cyclic oligomers, and crosslinking. We are reporting an improved one-pot synthesis coupled with an in-situ purification step of the monomer (as confirmed by 31P NMR) with little excess PCl5 in mole ratio (1:4.6-1:4.8). Further, the stability of PDCP and its solutions in toluene and THF have been examined under an inert atmosphere at three different temperatures: room temperature, 0 degrees C-4 degrees C, and -25 degrees C. These stored samples were monitored for cross-linking, gelling, or any other degradation by characterizing through 31P NMR for the appearance of additional peaks. The PDCP can be stored at -25 degrees C for 2 months (pure) and 4 months (toluene) without any deterioration in its structure.
Keywords: P-trichloro-N-(dichloromonophosphoryl)monophosphazene; Polycondensation; Polydichlorophosphazene; stability in solution; storage life